2019
DOI: 10.1108/jadee-02-2018-0032
|View full text |Cite
|
Sign up to set email alerts
|

Wholesalers perspectives on mango supply chain efficiency in India

Abstract: Purpose The purpose of this paper is to identify the factors and most significant reasons leading to supply chain inefficiency with respect to high cost, high lead time and poor quality at wholesale stage of mango supply chain in India, and also to find out the measures which may be taken to improve supply chain efficiency. Design/methodology/approach The paper opted for an exploratory study using the quantitative and qualitative method of research. The study was conducted at Asia’s largest and world’s secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…The study also highlighted the need and value of an efficient supply chain for better planning and management of the F&V sector to reduce losses and waste. Negi and Anand (2019, 2018) again conducted the studies on supply chain efficiency related to selected F&V and identified the reasons for supply chain inefficiency concerning three major factors, i.e. time, cost and quality.…”
Section: Past Studies On Supply Chain Efficiencymentioning
confidence: 99%
“…The study also highlighted the need and value of an efficient supply chain for better planning and management of the F&V sector to reduce losses and waste. Negi and Anand (2019, 2018) again conducted the studies on supply chain efficiency related to selected F&V and identified the reasons for supply chain inefficiency concerning three major factors, i.e. time, cost and quality.…”
Section: Past Studies On Supply Chain Efficiencymentioning
confidence: 99%
“…Based on the findings, it was concluded that the price of fresh and raw vegetables is determined in the wholesale market. Negi and Anand [48] examined the wholesale stage of a mango SC in India using factor analysis. Various factors affecting cost, lead time and quality and, therefore, causing inefficiency in the system, were eventually identified.…”
Section: Value Chain Indicators Of Ffvscsmentioning
confidence: 99%
“…The adequacy of the data for an exploratory factor analysis has been assessed through Kaiser–Meyer–Olkin (KMO) and the Bartlett's test of sphericity (Sharma and Gupta, 2015; Dhochak and Sharma, 2016; Singla et al , 2018). The KMO values which are higher than 0.6 are considered as satisfactory to carry out the factor analysis (Singh and Singh, 2018; Negi and Anand, 2019). Table 2 shows that the KMO value is 0.975, revealing that the data are fit for the factor analysis.…”
Section: Empirical Study Of Prioritizing the Barriers Toward The Successful Implementation Of Agile Manufacturingmentioning
confidence: 99%